2015
DOI: 10.1111/jan.12763
|View full text |Cite
|
Sign up to set email alerts
|

From student to graduate: longitudinal changes in the qualities of nurses

Abstract: This unique longitudinal study of Australian nurses suggests that the clinical experience and theoretical grounding provided in our University programs, has resulted in an increasing cumulative effect in the third year supporting most qualities of nurses/nursing understood in year 1, that is, the career fit to perceptions, has been achieved. The decline in the 1(st) year of graduation, where the concept of workplace misfit is occurring, is where further nurse graduate support is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…Exposure to the process of nurse education seemed to shift students' focus, especially at the end of the second year of education, once all students had completed their first internship in clinical practice. This is in line with the results of previous studies which showed that classroom and clinical experiences enhance the professional features of nursing and ensured that students recognized more fundamentally what nursing really entails (Cowin and Johnson, 2015;Day et al, 2005;Tseng et al, 2013). The first-year students in the study by Grainger and Bolan (2006) saw nurses as nice people who feel good about what they are doing, while fourth-year students were more focused on the professional roles of nurses.…”
Section: Changes In Orientation and Attitudes Towards Nursingsupporting
confidence: 89%
See 1 more Smart Citation
“…Exposure to the process of nurse education seemed to shift students' focus, especially at the end of the second year of education, once all students had completed their first internship in clinical practice. This is in line with the results of previous studies which showed that classroom and clinical experiences enhance the professional features of nursing and ensured that students recognized more fundamentally what nursing really entails (Cowin and Johnson, 2015;Day et al, 2005;Tseng et al, 2013). The first-year students in the study by Grainger and Bolan (2006) saw nurses as nice people who feel good about what they are doing, while fourth-year students were more focused on the professional roles of nurses.…”
Section: Changes In Orientation and Attitudes Towards Nursingsupporting
confidence: 89%
“…However, the changes over time showed nonlinear patterns. The patterns fluctuated over time for both orientation and attitude, which is consistent with the study by Cowin and Johnson (2015). The results of their longitudinal study on the qualities of nurses also showed great fluctuations in changes over a period of four years.…”
Section: Changes In Orientation and Attitudes Towards Nursingsupporting
confidence: 84%
“…However, the Australian study conducted by Cowin & Johnson (2015) identified graduate nursing qualities such as knowledge and respect for the profession declined in the graduate year. Qualities required in the transition time are not retained after the graduate year, highlighting the need for preceptor education and support to ensure longer term graduate transition.…”
Section: Discussionmentioning
confidence: 99%
“…New graduate nurses are entering a challenging workforce, in a time where staffing shortages, increased patient acuity, and inadequacy of resource availability are commonplace (Schwartz et al, 2011;Scott, et al, 2008). Scott et al (2008) consider new graduate nurse recruitment and retention as essential for staffing and supporting the health care system; however, much of the literature cites new graduate nurse attrition as an issue (Boamah & Laschinger, 2016;Bowles & Candela, 2005;Cowin & Johnson, 2015;McCloughen & O'Brien, 2005;Parker et al, 2014;Zinsmeister & Schafer, 2009).…”
Section: The New Graduate Nurse Experience: What We Knowmentioning
confidence: 99%